2010
DOI: 10.1332/174426410x535846
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of consulting research evidence among policy analysts in government ministries: a cross-sectional survey

Abstract: This large cross-sectional survey of policy analysts working in Quebec ministries (Canada) shows that direct interactions with academic researchers are among the most significant correlates of the consultation of scientific articles, academic research reports and academic books/chapters, but by very little compared to other correlates such as reported access to electronic bibliographic databases, training type, continuing professional development and perceived relevance of research evidence. Many correlates we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 0 publications
3
48
0
Order By: Relevance
“…First, given the professional tasks of these individuals, they can be considered as potential entry points for research evidence and possible channels of communication (Cohn, 2007;Howlett, 2009a;Nutley, Walter, & Davies, 2007;Ouimet et al, 2010;Sundell, Wärngård, & Head, 2013). To a certain extent, these professionals can be considered to act as informal knowledge brokers in that they absorb, interpret, and communicate external knowledge (Howlett, 2011).…”
Section: Knowledge Mobilization Theories and Assumptionsmentioning
confidence: 99%
“…First, given the professional tasks of these individuals, they can be considered as potential entry points for research evidence and possible channels of communication (Cohn, 2007;Howlett, 2009a;Nutley, Walter, & Davies, 2007;Ouimet et al, 2010;Sundell, Wärngård, & Head, 2013). To a certain extent, these professionals can be considered to act as informal knowledge brokers in that they absorb, interpret, and communicate external knowledge (Howlett, 2011).…”
Section: Knowledge Mobilization Theories and Assumptionsmentioning
confidence: 99%
“…Currently, as noted previously in this thesis, there is no universally accepted or widely adopted model for measuring the utilisation of research (Lester, 1993;Oh & Rich, 1996;Ouimet et al, 2010;Smith et al, 2011). The literature on the utilisation of academic research has, however, consistently suggested three broad types of use: instrumental, conceptual, and symbolic.…”
Section: Dependent Variable For Regression Modelsmentioning
confidence: 95%
“…(Lester, 1993;Oh & Rich, 1996;Ouimet et al, 2010;Smith et al, 2011) As highlighted in chapter one, there are many ways that research utilisation can be understood. While there have been some efforts to develop a standardised tool for measuring research utilisation -most notably Knott and Wildavsky's (1980) scale, which incorporates instrumental, conceptual and symbolic uses of researchsuch tools have not been widely employed to date.…”
Section: The Evidence-base For Linkagesmentioning
confidence: 99%
See 1 more Smart Citation
“…This is one measure of research utilisation that has been used by others (Cherney et al, 2015) and is an alternative to the Research Utilisation (RU) scale used by Landry (Landry, Amara, & Lamari, 2001a) and the three types of research use -instrumental, political and conceptual -identified by Weiss (1977). The benefit of using this measure over other measures is that it is important to be as factual as possible when asking policy officials their level of engagement with research outputs, and to use a timeframe that is not too long to better enable recall of certain activities (Ouimet et al, 2010).…”
Section: Constraints Associated With Academiamentioning
confidence: 99%